2023
DOI: 10.3389/fmars.2023.1145048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification and eutrophication on the growth and photosynthetic performances of a green tide alga Ulva prolifera

Abstract: With the impact of fossil fuel burning and industrialization, atmospheric CO2 concentration will reach about 1000 ppmv in 2100, and more and more CO2 will be absorbed by ocean, resulting in ocean acidification. The Chinese coastal waters are showing unexpectedly high levels of acidification due to a combination of global ocean acidification and severe regional eutrophication, which is caused by natural accumulation or human activities such as aquacultural tail water input, potentially affecting macroalgal bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…These show that fatty acids significantly influence stress and the control of biological responses and that these pathways are essential to the environmental adaptability and growth of algae [ 59 ]. Particularly acidifying circumstances significantly affect the levels of polyunsaturated fatty acids and palmitic acid [ 38 ].…”
Section: Allelochemicals and Allelopathy Mechanisms In The Green Tide...mentioning
confidence: 99%
See 1 more Smart Citation
“…These show that fatty acids significantly influence stress and the control of biological responses and that these pathways are essential to the environmental adaptability and growth of algae [ 59 ]. Particularly acidifying circumstances significantly affect the levels of polyunsaturated fatty acids and palmitic acid [ 38 ].…”
Section: Allelochemicals and Allelopathy Mechanisms In The Green Tide...mentioning
confidence: 99%
“…On the other hand, eutrophication and acidification of the ocean have proven green macroalgae to be remarkably adaptive [ 81 ]. In these situations, algal physiological regulating ability is increased in part by phenolic substances [ 38 ]. Furthermore, some research has demonstrated that green macroalgae can successfully regulate the amount of cyanobacteria by producing phenolic chemicals [ 82 ].…”
Section: Allelochemicals and Allelopathy Mechanisms In The Green Tide...mentioning
confidence: 99%
“…In addition to the aforementioned anthropogenic factors, it is also important to consider that U. prolifera absorbs a significant amount of nutrients such as nitrogen and phosphorus from seawater to support its growth and reproduction during the growing phase, and releases substantial amounts of carbon, nitrogen, and phosphorus back into the seawater during the decaying phase [71,72]. We posit that the timing and magnitude of U. prolifera harvesting may influence the degree of seawater eutrophication, thus affecting the scale of U. prolifera blooms in the subsequent year.…”
Section: Human Factors Analysismentioning
confidence: 99%
“…The ocean carbon cycle community is increasingly recognizing coastal and nearshore areas as hotspots for carbon and biogeochemical variability (Cai et al, 1998;Cai et al, 2020;Cai et al, 2021;Dai et al, 2022), especially vulnerable to global change, likely sites for marine CO 2 removal interventions, and regions of great importance, as coastal ecosystems provide invaluable resources and services, including various for climate change mitigation (Duarte et al, 2013b). The increased CO 2 uptake of coastal waters is not only contributing to their acidification but also exacerbating existing global challenges such as eutrophication, pollution, and habitat degradation (Andersson and Gledhill, 2013;Cai et al, 2023). Therefore, a robust understanding of carbonate chemistry is key to properly assessing habitat vulnerability to ocean acidification.…”
Section: Introductionmentioning
confidence: 99%